2022
DOI: 10.2147/dmso.s369824
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metabolic Dysfunction-Associated Fatty Liver Disease and the Risk of Cirrhosis in Patients with Chronic Hepatitis B—A Retrospective Cohort Study

Abstract: Background Metabolic dysfunction-associated fatty liver disease (MAFLD) is a novel proposed concept that is being recognized worldwide. Both chronic hepatitis B (CHB) and MAFLD have been independently attributed to an increased risk of disease development to cirrhosis. However, it is still unclear whether MAFLD is associated with an increased risk of cirrhosis in CHB patients. Aim This study aimed to analyze the impact of MAFLD on the risk of cirrhosis in CHB patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Compared with those without MAFLD, patients with MAFLD had higher hemoglobin [127 (108-144. (6)(7)(8)(9)(10)(11)(12)(13)(14) vs. 8.3 (5.7-12.5), P = 0.016] except that there were significant differences in the components of diagnostic MAFLD. In terms of liver-related complications, non-MAFLD patients were more likely to be accompanied by history of variceal hemorrhage [40 (21.6) vs. 88 (34.6), P = 0.005].…”
Section: Patient Characteristicsmentioning
confidence: 88%
See 1 more Smart Citation
“…Compared with those without MAFLD, patients with MAFLD had higher hemoglobin [127 (108-144. (6)(7)(8)(9)(10)(11)(12)(13)(14) vs. 8.3 (5.7-12.5), P = 0.016] except that there were significant differences in the components of diagnostic MAFLD. In terms of liver-related complications, non-MAFLD patients were more likely to be accompanied by history of variceal hemorrhage [40 (21.6) vs. 88 (34.6), P = 0.005].…”
Section: Patient Characteristicsmentioning
confidence: 88%
“…The definition of MAFLD allows for the incorporation of multiple causes of liver disease, this uniqueness of the definition of MAFLD allowed us to investigate the interaction between CHB and MAFLD, especially in the context of the high incidence of CHB and fatty liver in the Asian region [12]. In fact, a previous study has shown that the presence of MAFLD in patients with CHB was significantly associated with an increased risk of liver-related clinical events and death, and MAFLD also increased the probability of developing cirrhosis in patients with CHB [7,13]. It was acknowledged that NAFLD was a liver component of a series of diseases related to metabolic dysfunction and could progress to liver fibrosis, cirrhosis and portal hypertension, which significantly increased liver-related mortality and the risk of complications such as ascites, hepatic encephalopathy, variceal bleeding [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the association between MAFLD and higher risk of cirrhosis observed in a retrospective cohort study from China [ 26 ], and given reports that a growing percentage of cirrhosis cases in coming decades will occur in individuals with non-alcoholic fatty liver disease [ 27 ], we recommend careful assessment of comorbidities and liver function in HCC patients before hepatectomy. This may be particularly important for patients chronically infected with hepatitis virus, since those patients in our study showed higher prevalence of cirrhosis, portal hypertension, and ascites than patients with MAFLD but without chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…This subsequently enhances HBV replication by bile-acid-mediated repression of some interferon-stimulated genes, [24][25][26] and can increase the risk of cirrhosis in patients with CHB. 27 The discrepancy may reflect the complexity of HBV infection combined with NAFLD in clinical practice and basic research. Therefore, more studies are needed to further explore the effect of HS on HBV infection.…”
Section: Discussionmentioning
confidence: 99%